As the world burns : the new generation of activists and the landmark legal fight against climate change - Van der Voo, Lee (Timber Press, 2020)
"Award-winning investigative journalist Lee Van der Voo reports on Juliana v. the United States. Combining unparalleled access to the plaintiffs and reporting on the natural disasters that form an urgent backdrop to the story, van der Voo shares a timely and important story about the environment, the law, and the new generation of activists."--Provided by publisher.